Logarithm Rules

The base b logarithm of a number is the exponent that we need to raise the base in order to get the number.

Logarithm definition

When b is raised to the power of y is equal x:

b y = x

Then the base b logarithm of x is equal to y:

logb(x) = y

For example when:

24 = 16

Then

log2(16) = 4

Logarithm as inverse function of exponential function

The logarithmic function,

y = logb(x)

is the inverse function of the exponential function,

x = by

So if we calculate the exponential function of the logarithm of x (x>0),

f (f -1(x)) = blogb(x) = x

Or if we calculate the logarithm of the exponential function of x,

f -1(f (x)) = logb(bx) = x

Natural logarithm (ln)

Natural logarithm is a logarithm to the base e:

ln(x) = loge(x)

When e constant is the number:

e=\lim_{x\to \infty }(1+\frac{1}{n})^{n}=\lim_{x\to 0 }(1+n)^\frac{1}{n}=2.71828183...

 

See: Natural logarithm

Inverse logarithm calculation

The inverse logarithm (or anti logarithm) is calculated by raising the base b to the logarithm y:

x = log-1(y) = b y

Logarithmic function

The logarithmic function has the basic form of:

f (x) = logb(x)

Logarithm rules

Rule name Rule
Logarithm product rule
logb(x ∙ y) = logb(x) + logb(y)
Logarithm quotient rule
logb(x / y) = logb(x) - logb(y)
Logarithm power rule
logb(x y) = y ∙ logb(x)
Logarithm base switch rule
logb(c) = 1 / logc(b)
Logarithm base change rule
logb(x) = logc(x) / logc(b)
Derivative of logarithm
f (x) = logb(x) f ' (x) = 1 / ( x ln(b) )
Integral of logarithm
logb(x) dx = x ∙ ( logb(x) - 1 / ln(b) ) + C

Logarithm of negative number
logb(x)is undefined when x≤ 0
Logarithm of 0
logb(0) is undefined
\lim_{x\to 0^+}\textup{log}_b(x)=-\infty
Logarithm of 1
logb(1) = 0
Logarithm of the base
logb(b) = 1
Logarithm of infinity
lim logb() = ∞,when x→∞

See: Logarithm rules

 

Logarithm product rule

The logarithm of the multiplication of x and y is the sum of logarithm of x and logarithm of y.

logb(x ∙ y) = logb(x) + logb(y)

For example:

log10(37) = log10(3) + log10(7)

Logarithm quotient rule

The logarithm of the division of x and y is the difference of logarithm of x and logarithm of y.

logb(x / y) = logb(x) - logb(y)

For example:

log10(3 / 7) = log10(3) - log10(7)

Logarithm power rule

The logarithm of x raised to the power of y is y times the logarithm of x.

logb(x y) = y ∙ logb(x)

For example:

log10(28) = 8log10(2)

Logarithm base switch rule

The base b logarithm of c is 1 divided by the base c logarithm of b.

logb(c) = 1 / logc(b)

For example:

log2(8) = 1 / log8(2)

Logarithm base change rule

The base b logarithm of x is base c logarithm of x divided by the base c logarithm of b.

logb(x) = logc(x) / logc(b)

For example, in order to calculate log2(8) in calculator, we need to change the base to 10:

log2(8) = log10(8) / log10(2)

See: log base change rule

Logarithm of negative number

The base b real logarithm of x when x<=0 is undefined when x is negative or equal to zero:

logb(x) is undefined when x ≤ 0

See: log of negative number

Logarithm of 0

The base b logarithm of zero is undefined:

logb(0) is undefined

The limit of the base b logarithm of x, when x approaches zero, is minus infinity:

\lim_{x\to 0^+}\textup{log}_b(x)=-\infty

See: log of zero

Logarithm of 1

The base b logarithm of one is zero:

logb(1) = 0

For example, teh base two logarithm of one is zero:

log2(1) = 0

See: log of one

Logarithm of infinity

The limit of the base b logarithm of x, when x approaches infinity, is equal to infinity:

lim logb(x) = ∞, when x→∞

See: log of infinity

Logarithm of the base

The base b logarithm of b is one:

logb(b) = 1

For example, the base two logarithm of two is one:

log2(2) = 1

Logarithm derivative

When

f (x) = logb(x)

Then the derivative of f(x):

f ' (x) = 1 / ( x ln(b) )

See: log derivative

Logarithm integral

The integral of logarithm of x:

logb(x) dx = x ∙ ( logb(x) - 1 / ln(b) ) + C

For example:

log2(x) dx = x ∙ ( log2(x) - 1 / ln(2) ) + C

Logarithm approximation

log2(x) ≈ n + (x/2n - 1) ,

Logarithm problems and answers

Problem #1

Find x for

log2(x) + log2(x-3) = 2

Solution:

Using the product rule:

log2(x∙(x-3)) = 2

Changing the logarithm form according to the logarithm definition:

x∙(x-3) = 22

Or

x2-3x-4 = 0

Solving the quadratic equation:

x1,2 = [3√(9+16) ] / 2 = [35] / 2 = 4,-1

Since the logarithm is not defined for negative numbers, the answer is:

x = 4

Problem #2

Find x for

log3(x+2) - log3(x) = 2

Solution:

Using the quotient rule:

log3((x+2) / x) = 2

Changing the logarithm form according to the logarithm definition:

(x+2)/x = 32

Or

x+2 = 9x

Or

8x = 2

Or

x = 0.25

Graph of log(x)

log(x) is not defined for real non positive values of x:

Logarithms table

x log10x log2x logex
0 undefined undefined undefined
0+ - ∞ - ∞ - ∞
0.0001 -4.000000 -13.287712 -9.210340
0.001 -3.000000 -9.965784 -6.907755
0.01 -2.000000 -6.643856 -4.605170
0.1 -1.000000 -3.321928 -2.302585
1 0.000000 0.000000 0.000000
2 0.301030 1.000000 0.693147
3 0.477121 1.584963 1.098612
4 0.602060 2.000000 1.386294
5 0.698970 2.321928 1.609438
6 0.778151 2.584963 1.791759
7 0.845098 2.807355 1.945910
8 0.903090 3.000000 2.079442
9 0.954243 3.169925 2.197225
10 1.000000 3.321928 2.302585
20 1.301030 4.321928 2.995732
30 1.477121 4.906891 3.401197
40 1.602060 5.321928 3.688879
50 1.698970 5.643856 3.912023
60 1.778151 5.906991 4.094345
70 1.845098 6.129283 4.248495
80 1.903090 6.321928 4.382027
90 1.954243 6.491853 4.499810
100 2.000000 6.643856 4.605170
200 2.301030 7.643856 5.298317
300 2.477121 8.228819 5.703782
400 2.602060 8.643856 5.991465
500 2.698970 8.965784 6.214608
600 2.778151 9.228819 6.396930
700 2.845098 9.451211 6.551080
800 2.903090 9.643856 6.684612
900 2.954243 9.813781 6.802395
1000 3.000000 9.965784 6.907755
10000 4.000000 13.287712 9.210340

 

Logarithm calculator ►

 


See also

Write how to improve this page

  URL
  Name
  E-mail